1998
DOI: 10.1095/biolreprod58.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Withdrawing Long Days from Male American Tree Sparrows (Spizella Arborea): Implications for Understanding Thyroid-Dependent Programming of Seasonal Reproduction and Postnuptial Molt1

Abstract: In previous studies, we withdrew thyroid hormones by thyroidectomy before, at, or after the onset of photostimulation and showed that male American tree sparrows (Spizella arborea) are programmed for seasonal reproduction and postnuptial molt by or before Week 3 on long days. In this corollary study, we withdrew long days before or after the control circuits had been programmed. After 1 day to 4 wk on long days, groups of thyroid-intact males were returned to short days until Week 7, when they were moved to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…When photorefractoriness is induced, production and release of GnRH are both attenuated (Parry et al, 1997), accompanied by regression of sexual gonads (Pingel, 1990). Wilson and Reinert (1998) also indicated that photorefractoriness and postnuptial molt were both induced by long length of light day.…”
Section: Introductionmentioning
confidence: 92%
“…When photorefractoriness is induced, production and release of GnRH are both attenuated (Parry et al, 1997), accompanied by regression of sexual gonads (Pingel, 1990). Wilson and Reinert (1998) also indicated that photorefractoriness and postnuptial molt were both induced by long length of light day.…”
Section: Introductionmentioning
confidence: 92%